(untitled) (Materiali di Estetica. Terza serie, 2020)
Europe is a complex reality which cannot easily be defined given the fragmentation of the elements that compose it. Actually, the individual cultures have historically been constituted through relatively recent identity rites. In this article some moments of the formation of these identities are examined, relating to the melodrama during the French revolution on one side, and to the nineteenth-century "rites" of German nationalism, on the other. The paper then deals with the Nazism which made a wide use of the same kind of rituality and with some farcical developments in the contemporary Italy. These elements too are linked in various ways to German rituality. In all these cases the aesthetic dimension is eminent as an instrument of government. Its meaning should be deepened.